MENYINGKAP IDEOLOGI PATRIARKI DALAM KISAH 1001 MALAM: KAJIAN DEKONSTRUKTIF - Syam, Essy; Aris, Qori Islami (Jurnal Ilmu Budaya, 2021)
This writing analyzes a popular Malay text entitled Kisah 1001 Malam (Arabian Nights). This analysis shows that from the perspective of patriarchal ideology, a man is signified as a strong and powerful figure. On the other hand, the analysis shows that the strong and powerful figure in the text is not the man but a woman instead. It is shown by presenting the man character who fails to fulfill his role as the savior or the problem solver, thus, the role is taken by a woman character. Thus, this analysis applies descriptive analysis in which the result of the analysis is described vividly. From the description, it will show patriarchal ideology which places man as the powerful figure is replaced by a woman who is strong and smart.